B.G. Prasad Scale 2025: An Updated Framework for Socioeconomic Assessment in India - Aanchal Anand; Irena Mandal; Samar Hossain (National Journal of Community Medicine)
The B.G. Prasad Socioeconomic Classification has been a cornerstone in assessing the socioeconomic status (SES) of Indian households since 1961. Periodic updates using the Consumer Price Index for Industrial Workers (CPI-IW) ensure its continued relevance. Given the changing economic conditions and inflation trends, periodic updates are necessary. The CPI-IW for January 2025 is 143.2, necessitating a recalculation of the income thresholds. This study aims to update the B.G. Prasad Scale for 2025 using the latest Consumer Price Index for Industrial Workers (CPI-IW), analyze the impact of inflation on socioeconomic classification, and assess its implications in public health and policymaking. The updated classification is calculated using the base values from 1961, linking factors from previous updates (1982, 2001, 2016), and the latest CPI-IW. The calculation steps are outlined to ensure transparency and reproducibility. The Modified B.G. Prasad Scale 2025 ensures that socioeconomic classification remains relevant. However, limitations such as its income-centric approach highlight the need for a multidimensional SES framework. Future updates should incorporate education, occupation, and regional adjustments to enhance its applicability in public health research and policy development.